The Effectiveness of Archival Training in Improving Archive Literacy in Teachers and Students of SMK Negeri 1 Kisaran - Sri Mutmainnah; Rotua SP Simanullang; Ellys Siregar; Gartima Sitanggang (International Journal of Advanced Research, 2024)
Archive literacy is an essential competency in supporting effective information management in various fields, including education. However, the low level of archive literacy among teachers and students is one of the main challenges in document management in vocational high school, including at SMK N1 Kisaran. This research aims to evaluate the effectiveness of archival training in improving archive literacy in teachers and students. The research used a quantitative method with a pre-test and post-test design, involving 30 participants consisting of teachers and students. The training included theory and practice sessions on manual and digital archive management. The results of the research showed a significant increase in participants' archive literacy, both in terms of knowledge, skills, and attitudes towards archive management. The average archive literacy score increased by 35% after the training. In addition, this training also succeeded in increasing awareness of the importance of systematic archive management to support work efficiency and fluency of school administration. This research concludes that archival training is an effective strategy to improve archival literacy, especially in vocational education environments. Recommendations include the development of more comprehensive and sustainable training programs to support the needs of archival literacy in the school.